Reading the Roman republic in early modern England - Cox Jensen, Freyja, 1984- (Library of the written word ;, 2012)
Placing the reading of history in its cultural and educational context, and examining the processes by which ideas about ancient Rome circulated, this study provides the first assessment of the significance of Roman history, broadly conceived, in early modern England.